PENGGUNAAN EKSTRAK AKAR TUBA (Derris elliptica) DENGAN DOSIS YANG BERBEDA DALAM PENGANGKUTAN IKAN PATIN SISTEM TERTUTUP - Dini Puspa Monica; Mochamad Syaifudin; Sefti Heza Dwinanti (Universitas Sriwijaya, 2020)
The transportation process can lead to stress which increases mortality in fish. Efforts to reduce mortality in the process of fish transportation can be conducted by minimizing the metabolic activities of fish during transportation. One of the natural substances that is used for fish transportation is tuba roots. The aim of this study is to determine the effect of different dosages of tuba root extract on the transport of catfish seeds with a closed transport system for 12 hours. This research was conducted at the Aquaculture Laboratory, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University. The research was conducted in April 2019. This study used a completely randomized design (CRD) method with four different dosage treatments (T) and three replications. The dosages of tuba root extract were: 0 ml.L-1 (T0), 0.05 ml.L-1 (T1), 0.10 ml.L-1 (T2), 0.15 ml.L-1 (T3). The parameters observed were blood glucose levels, water quality, survival of catfish after transportation and maintenance for 7 days. The results showed that T1 (0,05 ml.L-1) was gave the highest survival rate of 91.66±2.88%, with the lowest stress level indicated by blood glucose values 89±30.63. In addition, there was no further effect from the administration of tubal root extracts to protect the life of the fish after transportation and maintenance.Keywords : Tuba root, catfish, transportation